Cavernous sinus thrombosis as a rare cause of exophthalmos in childhood : A case report - Kamawal, A.; Schmidt, M. A.; Rompel, O.; Gusek-Schneider, G. C.; Mardin, C. Y.; Trollmann, Regina (Ophthalmologe, 2016)
Complications of acute bacterial sinusitis mostly occur in children and adolescents. In particular, intracranial spread of the infection can lead to severe even fatal courses of the disease. This article is a case report about a 13-year-old boy suffering from left-sided headache, meningismus and exophthalmos as presenting symptoms. Cranial magnetic resonance imaging (MRI) showed merely right-sided sphenoid sinusitis; however, the diffusion-weighted MRI sequence indicated a left-sided cavernous sinus thrombosis, which could be confirmed by computed tomography (CT) angiography. Cerebrospinal fluid diagnostics showed significant leukocytosis confirming secondary meningitis. Finally, exophthalmos was explained by parainfectious cavernous sinus thrombosis and periorbital edema. This case report highlights the importance of extended and specific diagnostic imaging in cases of clinically suspected complications in children and adolescents with sinusitis and the diagnostic significance of diffusion-weighted MRI.
EVALuna2:21321